Hantu Perempuan sebagai “Produk Gagal” dalam dua Film Horor Indonesia: Pengabdi Setan (2017) dan Asih (2018) - Shita Dewi Ratih Permatasari; Ni Made Widisanti (Media Bahasa, Sastra, dan Budaya Wahana, 2019)
AbstractAs a product of popular culture, films are mostly utilized as propaganda to convey certain ideologies. Therefore, the cultural phenomena and reality portrayed in films cannot be separated from the dominant ideology. “Pengabdi Setan” 2017 (Satan’s Slave) and “Asih” 2018 are two Indonesian horror films serving as media to represent the cultural phenomena through female ghost characters. In many Indonesian horror movies, women are mostly represented as ghosts associated with negative social attributes. The purpose of this research is to dismantle the hidden ideologies behind the representation of female ghosts in these two films. The qualitative method and cultural studies perspective are utilized to reveal and unearth the dominant ideology inserted in a film as a cultural text. The research findings posit that the characters of female ghosts are represented as a ‘failed product” excluded from the constructions of “ideal” female in patriarchal sense. The image of mother as a ghost in Pengabdi Setan implies that to become ‘ideal”, women must be able to give birth and raise children, while in Asih a woman is claimed to keep their virginity until she officially gets married. In this context, marriage and procreative sexuality are acknowledged by the state. Both female characters in these films have failed to meet these qualifications. Through these two Indonesian horror films, patriarchy as a dominant view in Indonesia is again conformed and exercised in the society to define the female ‘ideal’ construction.Keywords: horror films, representation, female ghost, patriarchy.